2016
DOI: 10.1590/abd1806-4841.20165138
|View full text |Cite
|
Sign up to set email alerts
|

Premature ventricular contractions associated with isotretinoin use

Abstract: Isotretinoin has been considered a unique drug for acne treatment. However, it is associated with numerous adverse effects. Isotretinoin can trigger premature ventricular contractions. This report describes a 33-year-old-woman who presented with palpitations for 1 week while undergoing 1-month isotretinoin treatment for mild-moderate facial acne. An electrocardiogram and Holter monitoring showed premature ventricular contractions during isotretinoin (Roaccutane, Roche) treatment. Isotretinoin-related premature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In a study conducted in 45 patients receiving isotretinoin treatment for 6 months due to acne vulgaris, Dursun et al observed no difference in QTc and QT dispersion, which is an indicator of malign ventricular arrhythmia, and in these patients it was safe in terms of ventricular arrhythmia for 6 months of acne treatment [21]. Although rare, in the literature there are cases indicating that isotretinoin can cause ventricular extrasystole and atrial tachycardia attacks [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in 45 patients receiving isotretinoin treatment for 6 months due to acne vulgaris, Dursun et al observed no difference in QTc and QT dispersion, which is an indicator of malign ventricular arrhythmia, and in these patients it was safe in terms of ventricular arrhythmia for 6 months of acne treatment [21]. Although rare, in the literature there are cases indicating that isotretinoin can cause ventricular extrasystole and atrial tachycardia attacks [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PVCs are extra, abnormal heartbeats with a wide and abnormal QRS complex, without a preceding P wave; they can result from hypoxia, hypovolemia, electrolyte abnormalities, medications, or irritation from intracardiac monitoring or pacing catheters; they can also be idiopathic in nature. 6 The PVCs can be serious in themselves if they are numerous, repetitive, and there are several outbreaks of excitement, especially in heart disease, where they can cause tachycardia or atrial fibrillation with sometimes a risk of sudden death.…”
mentioning
confidence: 99%
“…In fact, PVCs are extra, abnormal heartbeats with a wide and abnormal QRS complex, without a preceding P wave; they can result from hypoxia, hypovolemia, electrolyte abnormalities, medications, or irritation from intracardiac monitoring or pacing catheters; they can also be idiopathic in nature. 6…”
mentioning
confidence: 99%